Clinical and videofluoroscopic outcomes of laparoscopic treatment for sliding hiatal hernia and associated gastroesophageal reflux in brachycephalic dogs. (9th March 2021) - Mayhew, Philipp D.; Balsa, Ingrid M.; Marks, Stanley L.; Pollard, Rachel E.; Case, J. Brad; Culp, William T.N.; Giuffrida, Michelle A
Abstract: Objective: To describe a laparoscopic technique for treatment of sliding hiatal hernia (SHH) and associated gastroesophageal reflux (GER) in brachycephalic dogs and document clinical and videofluoroscopic outcomes postoperatively. Study design: Prospective clinical trial. Animals: Eighteen client‐owned dogs. Methods: A three‐port laparoscopic approach was used. Intracorporeal suturing was used for hiatal plication and esophagopexy, and left‐sided laparoscopic or laparoscopic‐assisted gastropexy was performed. A standardized canine dysphagia assessment tool (CDAT) questionnaire was completed by owners pre‐ and postoperatively. Videofluoroscopic swallow studies (VFSS) were used to evaluate esophageal function, and impedance planimetry was used to assess lower esophageal sphincter geometry preoperatively and in a subset of dogs postoperatively. Results: Median age was 27.5 (range 5–84) months. Conversion to open surgery was necessary in 1 (5.5%) of 18 dogs. Regurgitation after eating, and associated with activity/exercise, improved significantly when comparing pre‐ and postoperative CDAT assessments. Hiatal hernia and GER severity scores improved significantly between pre‐ and postoperative VFSS assessments, whereas SHH and GER frequency scores did not. One dog developed pneumothorax intraoperatively, underwent cardiopulmonary arrest, and died. Minor complications included splenic ( n  = 6) and hepatic lacerations ( n  = 3) that did not require specific therapy. Conclusion: A laparoscopic approach to treatment of SHH and GER led to improvements in clinical and VFSS indices in the majority of brachycephalic dogs. However, a subset of dogs still demonstrated some clinical signs postoperatively. Clinical relevance: In experienced hands, laparoscopic treatment of SHH and GER offers a minimally invasive alternative to open surgery.